1975
DOI: 10.1113/jphysiol.1975.sp011084
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curare on the release of acetylcholine from mammalian motor nerve terminals and an estimate of quantum content.

Abstract: SUMMARY1. Curarized and non-curarized rat hemidiaphragm muscles were indirectly stimulated in vitro.2. The fluid bathing the active curarized muscles was eluted through a dextran gel (Sephadex G-10), effecting a complete separation of ACh from curare. The acetylcholine fraction was then assayed on an isometric leech muscle preparation.3. Prostaglandin (PGE1) in a concentration fifteen times that estimated to be released from the skeletal muscle preparation did not affect the response of leech muscle to ACh.4. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(49 citation statements)
references
References 31 publications
5
43
1
Order By: Relevance
“…Mitchell & Silver (1963) considered the amount 9 E. S. VIZI AND F. VYSKOCIL of ACh involved in m.e.p.p. production to be only 1-3 % and similarly, Fletcher & Forrester (1975) estimated the quantal spontaneous release in the rat diaphragm to be only 2 % of the total release. According to our data the resting quantal release represents in the mouse preparation not more than 10 % of the total amount of ACh, this value being close to previous estimates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitchell & Silver (1963) considered the amount 9 E. S. VIZI AND F. VYSKOCIL of ACh involved in m.e.p.p. production to be only 1-3 % and similarly, Fletcher & Forrester (1975) estimated the quantal spontaneous release in the rat diaphragm to be only 2 % of the total release. According to our data the resting quantal release represents in the mouse preparation not more than 10 % of the total amount of ACh, this value being close to previous estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Fletcher & Forrester (1975) calculated that no more than 2 % of the resting release of ACh could be responsible for the production of m.e.p.p.s.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that there is an appreciable secretion of ACh in a nonquantized form, particularly at rest (22,32). Recent estimates of the number of ACh molecules in a quantum range from 6 to 10 x 103 (12,25). If we assume a value of 8 x 10 a, then the rate of secretion of ACh due to quanta is 0.4 pmol/15 min for a resting hemidiaphragm (7,000 junctions, mean mepp frequency of 5/s).…”
Section: Release Of Achmentioning
confidence: 99%
“…If we assume that all of the extra ACh released by K is secreted as quanta, then we calculate the number of ACh molecules in a quantum to be 13 x 10 a, a figure only 30% greater than the upper limit estimated by Kuffler and Yoshikami (25). 1 When 25 mM K is applied in the presence of HC-3, the rate of release of ACh increases, but the increase is not sustained and the rate even-1 Fletcher and Forrester (12) have estimated the quantal size in rat diaphragms to be only 6 • 103 molecules. Their calculation assumed an epp to be composed of 400 quanta.…”
Section: Release Of Achmentioning
confidence: 99%
“…They concluded that curare had principally a postjunctional action. Since then several attempts have been made to study the prejunctional effect of (+)-tubocurarine (Chang et al, 1967;Fletcher & Forrester, 1975), but until now attempts to demonstrate the inhibitory effect of (+)-tubocurarine on the evoked release of ACh by neurochemical methods (i.e. assay of the released ACh) have been unsuccessful.…”
Section: Stimulationmentioning
confidence: 99%